Usefulness of Alvarado Score for the diagnosis of acute appendicitis in hospitals of poor resources - Ibrahim, Wisam Nabeel; Abdulrazzaq, Saad Mohammed (IIUM Press, 2019)
Background: The delay in diagnosing appendicitis is associated with a significant increase in mortality and morbidity among patients due to complications such as perforation, peritonitis and septicaemia. Therefore, Alvarado score is one of the tools used to diagnose appendicitis and reduce the probability of delayed diagnosis based on clinical and laboratory indicators. Objective: This study aimed to evaluate the precision of Alvarado score in diagnosing appendicitis among suspected patients in al-Wihda teaching hospital, Thamar University, Yemen. Methods: a total od 106 participants suspected of having appendicitis due to the clinical presentation were included in the study. Alvarado score was determined in each of the participants upon tier arrival to the emergency department of the hospital. Based on the follow up, histological examination and the intra operative observation the diagnosis was confirmed or excluded. The accuracy of the score was evaluated by calculating sensitivity, specificity, positive and negative predictive values and likelihood ratios. Results: The cut point of Alvarado score 8 was used in diagnosing appendicitis with 87% and 93% sensitivity and specificity respectively. The positive the likelihood ratio was 12 and the negative likelihood ratio was 0.14. Conclusion: Alvarado score is a promising criterion-based tool that would vitally help in early detection of appendicitis among patients. More efforts are required to improve precision of test and minimize the number of cases mistakenly diagnosed with appendicitis in hospitals with limited resources.